2021
DOI: 10.3390/ph14070610
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Anti-osteoarthritic Compounds of a Standardized Fraction from Sphaeralcea Angustifolia

Abstract: Sphaeralcea angustifolia has been widely used in inflammatory conditions such as blows, bruises, fractures, and wounds. The compounds identified as active in plants and suspension cell culture of S. angustifolia were tomentin, scopoletin, and sphaeralcic acid. To consolidate the integral use of knowledge about the S. angunstifolia and strengthen its pharmacological use in patients with knee osteoarthritis, the pharmacokinetic behavior of the active compounds was characterized. The SaTSS (S. angustifoloia stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The detection and time course of the compounds were followed in the plasma, urine, and feces of mice after a single oral dose (400 mg/kg) of the standardized fraction. The authors describe the extraction of the biomass and its chemical fractionation to obtain the standardized active fraction, HPLC analysis, and the extraction and stability of the active compounds based on the guidelines established by the FDA (Food and Drug Administration) for plasma samples [ 28 ]. The pharmacokinetic profile of the mixture of coumarins and sphaeralcic acid showed that these compounds were detected in mouse plasma, and no products of their biotransformation were registered.…”
Section: Experimental Studies On S Angustifoliamentioning
confidence: 99%
See 1 more Smart Citation
“…The detection and time course of the compounds were followed in the plasma, urine, and feces of mice after a single oral dose (400 mg/kg) of the standardized fraction. The authors describe the extraction of the biomass and its chemical fractionation to obtain the standardized active fraction, HPLC analysis, and the extraction and stability of the active compounds based on the guidelines established by the FDA (Food and Drug Administration) for plasma samples [ 28 ]. The pharmacokinetic profile of the mixture of coumarins and sphaeralcic acid showed that these compounds were detected in mouse plasma, and no products of their biotransformation were registered.…”
Section: Experimental Studies On S Angustifoliamentioning
confidence: 99%
“…It was determined that coumarins and sphaeralcic acid circulate to the white site and are subsequently detected in urine and feces. It was concluded that the mixture of scopoletin and tomentin are eliminated by the renal route and sphaeralcic acid by the enterohepatic route [ 28 , 29 ].…”
Section: Experimental Studies On S Angustifoliamentioning
confidence: 99%
“…It slows OA development by preventing chondrocytes from responding in a catabolic manner. Wnt/β‐catenin and ERK1/2–Runx2 pathways are activated when estrogen is present, inhibiting monocyte recruitment and bone formation (Serrano‐Román et al, 2021). Using oroxylin A, a flavonoid molecule produced from Oroxylum indicum , researchers could inhibit inflammation, prevent apoptosis, and fight tumors simultaneously.…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…The volume of distribution (Vd), mean residence time (MRT), elimination half-life (t 1/2 ), and area under the plasma concentration-time curve from 0 h to infinity (AUC inf ) were determined after intravenous administration of MeP-loaded NPs to animals. All calculations were performed using the PKSolver add-in program for Microsoft Excel [114].…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 99%